KAJI EKSPERIMENTAL PENYERAPAN ENERGI TABUNG ALUMINIUM YANG MENGALAMI BEBAN TEKAN ARAH AKSIAL - Hadi, Bambang K; Putra, Ichsan S; Tedy S, Yanyan (Mesin, 2006)
Energy absorbing structural components are widely used in vehicles, such as car, aircraft, train, ships and others. The aim is to absorb energy during impact and thus lessen the risk of occupantâs injuries and limit the damage to the whole structure. Cylindrical shell that deform plastically due to longitudinal loading is one of the efficient energy absorbing structures. In this paper, experiments were carried out on aluminum cylindrical shell which was loaded axially. The diameters of the cylindrical shell were 60 mm and 100 mm, and the thickness was 2 mm. Some collapse trigger mechanisms were investigated, which are: plastic fold trigger, circular hole trigger and oval hole trigger. The experiments will then be compared with analytical results.